Implementation of Professional Competence of Islamic Religious Education Teachers Towards the Achievement of Teaching Achievement of Grade IV Students of State Elementary School 1 Watiginanda, South Buton Regency - B, Fitria; Maudin, Maudin; Yahya, Safaruddin (Journal of English Language and Education, 2025)
This research aims to determine the implementation of the professional competence of Islamic religious education teachers (PAI) on the achievement of learning achievements of grade IV students of State Elementary School 1 Watiginanda, South Buton Regency. Teacher Professional Compensation is one of the important factors that influence PAI subjects which plays a role in shaping the character and spirituality of students. This study uses a qualitative approach with a descriptive type of research. Data collection techniques are carried out through observation, interviews, and documentation. The subjects of the study were PAI teachers and Grade IV students at SDN 1 Watiginda. The data obtained was analyzed qualitatively through the stages of data reduction, data presentation, and conclusion drawn.The results of the study show that the implementation of the professional competencies of PAI teachers at SDN 1 Watiginanda includes mastery of the material, learning strategies, and evaluation of learning outcomes. PAI teachers are able to apply their competencies quite well, which is shown by systematic and interesting planning and implementation of learning. This contributes positively to student learning achievement, which can be seen from increasing the average score of learning outcomes and students' enthusiasm in participating in PAI learning.Conclusion The professional competence of Islamic religious education teachers at SDN Negeri 1 Watiginanda has gone quite well and has had a positive impact on the learning achievement of grade IV students. Teachers who are able to master the material, use the right learning strategies, and conduct evaluations effectively, can improve the quality of learning and student learning outcomes. Therefore, the improvement of teachers' professional competence needs to continue to be carried out through training, supervision, and self-development so that the quality of religious education in elementary schools is more optimal.